Analysis of the Effects of Macroeconomic Variables on Non-Performing Credit Risk in Emerging Market Asia 2010-2018 - Dewi, Karina Puspa; Purwono, Rudi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2020)
The purpose of this study is to determine and analyze the influence of macroeconomic variables on the risk of non-performing loans with case studies in Emerging Markets Asia in the period 2010 to 2018. The risk of non-performing loans representing banking stability is measured using Non-Performing Loans (NPLs). Meanwhile, macroeconomic variables that represent economic stability consist of Gross Domestic Product (GDP), Exchange Rates, Loan Interest Rates, Inflation, and Domestic Credit to Private Sector. Data obtained online through the World Development Indicator Database is then estimated using dynamic panel regression or Generalized Method Of Moment (GMM). The results of this study indicate that the variable GDP, Exchange Rate, and Inflation negatively affect NPL. Meanwhile, variable interest rates on loans and the Domestic Credit to the Private Sector have a positive effect on NPLs. Keywords: Macroeconomic Variables, Non Perfoming Loan, GMM JEL: C30; F40